ANALISIS NILAI TAMBAH KERIPIK PISANG KEPOK DAN SISTEM PEMASARAN PISANG KEPOK(MUSA PARADISIACA) DI KABUPATEN PESAWARAN - Cahyawati, Novia; Arifin, Bustanul; Indriani, Yaktiworo (Jurnal Ilmu-Ilmu Agribisnis, 2020)
The purpose of this research was to analyze the added value of ?kepok? banana chips, banana marketing system, and to examine the marketing mix of kepok banana chips in agroindustry in Karang Anyar Village, Gedong Tataan District of Pesawaran Regency. The respondents consisted of five owners of banana chipsagroindustry, 12 banana traders, and 35 farmers. Data were collected in October - December 2018, and analyzed using qualitative and quantitative descriptive method. The results showed that chocolate banana chips has greater added value than original and caramel banana chips. The marketing system of Kepok banana is not efficient and tends to be oligopsonistics. The marketing mix in the Kepok banana chips agroindustry follows the four principles of product, prices, places, and promotions. However, location of agroindustry is not strategic and promotions useonly a personal selling method.Keywords: added value, banana chips, marketing.